The Implementation of Project Based Learning (PjBL) Based on STEM: A Reflection of Concept and Reality within Learning Process in Business Department of Vocational High School - Agung Winarno; Afidzatul Maulana (Department of Management, Faculty of Economics, Universitas Negeri Malang, 2020)
The 21st century education expects students to have the skills to solve problems, develop knowledge, be able to develop high degree of thinking and critical thinking. This expectation requires schools to be able to take an innovative learning approach. This study aims at determining the implementation of the STEM-based Project Based Learning (PjBL) model in General Administration subjects as well as how it impacts student learning outcomes. This research is a survey based on the implementation of Classroom Action Research (CAR) by the practicum teacher. This Classroom Action Research requirements that were included in the observation were at least two cycles with two meetings per cycle. The results showed that the implementation of the STEM-based Project Based Learning (PjBL) model of teachers experienced more problems related to the interpretation of each component of the planning process for the preparation of learning tools and specifically difficulties when the process of real-life context learning activities in class. However, this learning model provided benefits in strengthening participants to improve learning outcomes   Keywords: Learning Outcomes, STEM approach, Project Based Learning